استخدام الطفل لمياتف الذكي في السياق الأسري - خولة عطيات; نعيمة بمقاسمي; د/الجودي بن قيط (جامعة عمار ثليجي الاغواط, 2023)
ا ملخص الدراسة: جاءت دراستنا بعنوان استخدام الطفل للهاتف الذكي في السياق الاسري- دراسة على عينة من أطفال الاغواط ، وانطلقت دراستنا من الإشكالية: ما مدى استخدام الطفل للهاتف النقال الذكي في السياق الاسري ؟ نهدف من خلال دراستنا الى معرفة العلاقات الأسرية وتأثرها باستخدام الهاتف النقال سواء إيجابا أو سلبياو معرفة التأثير الكبير الذي تلعبه التكنولوجيا الحديثة المتمثلة في الهاتف النقال في حياة الاطفال. كما نهدف إلى تقديم واقتراح بعض النصائح والتوصيات التي من شأنها التخفيف من الآثار السلبية للهاتف النقال الذكي على الطفل والتعرف على أسباب استخدام الطفل للهاتف النقال ودوافع استخدامه له والتعرف على اثار وانعكاسات استخدام الطفل للهاتف الذكي عليه. حيث تم اعتماد على المنهج الوصفي لكون دراستنا دراسة وصفية عبر أداة جمع البيانات الاستبيان لدراسة عينتنا المتكونة من مجموعة من أطفال مدينة الاغواط والبالغ عددهم 30 طفلا حيث توصلنا الى النتائج التالية: 1. الطفل لديه ميول للعب والتسلية هذا الامر المنطقي لسن الطفولة ويساعد هذا على هدوءه وتعلقه بالهاتف نظرا للتسلية التي يحددها في الالعاب في البداية على اسا التعلم مثلا تعلم الحروف الاناشيد والارقام الا ان الطفل بعد مدة قليلة يتجه للتسلية واللعب فقط . 2. المستوى الذي وصل اليه الأبناء في استعمالهم للهاتف كبير، حيث صاروا يعرفون تنزيل الألعاب ومشاهدة افلام الكرتون، وفيديوهات الضحك والحيوانات والتسلية وعليه لا يرضون الا بوجود الانترنت في المنزل لاستخدام الهاتف. 3. كل الأولياء يعلمون مضار ومخاطر استعمال الطفل للهاتف من خلال الحصص التلفزيونية والحوارات العائلية والاجتماعية التي تدور حول هذا الموضوع وعليه يخضع غالبية الأولياء لطلبات أبنائهم حرضا على عدم بكائهم أو ارضاءهم وتجنب الفوضى ومكوث في المنزل وأيضا الراحة للأولياء. 4. استعمال الهاتف من طرف أبنائهم يكون بعلم اوليائهم، وهذا حرصا على الوقوف على درجة استعمال الطفل للهاتف، وأيضا خوفا على سلامة هواتفهم كنوع من الرقابة ولو القليلة على هذا الاستعمال لتجنب التأثيرات السلبية على ابنائهم جراء هذا الاستعمال. Abstract Our study came under the title of the child's use of the smart phone in the family context - a study on a sample of the children of Laghouat. Through our study, we aim to know the family relationships and their impact on the use of the mobile phone, whether positively or negatively, and to know the great impact that modern technology plays in the lives of children. We also aim to provide and suggest some tips and recommendations that will mitigate the negative effects of the smart mobile phone on the child, identify the reasons for the child’s use of the mobile phone and the motives for using it, and identify the effects and repercussions of the child’s use of the smart phone on him. Where the descriptive approach was adopted because our study is a descriptive study through the questionnaire data collection tool to study our sample consisting of a group of 30 children from the city of Laghouat, where we reached the following results: 1. The child has tendencies to play and have fun. This is logical for the age of childhood and this helps to calm him down and his attachment to the phone due to the entertainment that he sets in games at the beginning on the basis of learning, for example, learning letters, songs and numbers, but after a short period of time the child turns to entertainment and play only. 2. The level that children have reached in their use of the phone is great, as they know how to download games, watch cartoons, and videos of laughter, animals and entertainment, and therefore they are not satisfied except with the presence of the Internet at home to use the phone. 3. All parents are aware of the harms and dangers of the child’s use of the phone through television sessions and family and social dialogues that revolve around this subject. Therefore, the majority of parents submit to their children’s requests, urging them not to cry or please them, avoid chaos, stay at home, and also provide comfort for parents. 4. 4. The use of the phone by their children should be with the knowledge of their parents, and this is in order to find out the degree of the child’s use of the phone, and also for fear of the safety of their phones as a kind of control, even if little, on this use to avoid negative effects on their children as a result of this use.
د ا رسة عمى مجموعة من أولياء أطفال - بمدينة الاغواط